2021
DOI: 10.1097/tp.0000000000003664
|View full text |Cite
|
Sign up to set email alerts
|

An Intention-to-treat View of Lung Transplantation for Interstitial Lung Disease: Successful Strategies to Minimize Waiting List and Posttransplant Mortality

Abstract: Nine patients underwent late reoperation on >1 occasion, or for >1 indication. BOS, bronchiolitis obliterans syndrome; CLAD, chronic lung allograft dysfunction; FEV 1 , forced expiratory volume in 1 s; FVC, forced vital capacity; LTx, lung transplantation; mMRC, modified medical research council dyspnea scale; RAS, restrictive allograft syndrome; re-Tx, retransplantation; VATS, video-assisted thoracoscopic surgery. FIGURE 6. Cumulative incidence curve for chronic lung allograft dysfunction (CLAD) corrected for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Such distributional shifts in population capped the upper bounds in predictive accuracy of these variables. On the other hand, the higher donor lung availability [ 21 , 37 ] potentially allowed less severe CF patients in Canada to receive LTx, which resulted in the lower relevance between LTx and these markers of severe lung diseases. For instance, the risk factor of hospital stay got closer to the dashed line when only the single endpoint of death was considered in Fig 2(b) , which indicated nearly equal predictive power in the two populations compared to Fig 2(a) .…”
Section: Resultsmentioning
confidence: 99%
“…Such distributional shifts in population capped the upper bounds in predictive accuracy of these variables. On the other hand, the higher donor lung availability [ 21 , 37 ] potentially allowed less severe CF patients in Canada to receive LTx, which resulted in the lower relevance between LTx and these markers of severe lung diseases. For instance, the risk factor of hospital stay got closer to the dashed line when only the single endpoint of death was considered in Fig 2(b) , which indicated nearly equal predictive power in the two populations compared to Fig 2(a) .…”
Section: Resultsmentioning
confidence: 99%
“…The LTx group from Melbourne [ 8 ] compared the early- and mid-term outcomes of 31 IPF patients, in whom antifibrotics were continued until the day of LTx, to 71 IPF patients not on antifibrotics before LTx. The authors reported no bronchial anastomotic complications in either group and no difference in rates of reoperation for wound or bleeding complications [antifibrotic: 13% (4/31), control: 8.4% (6/71); P = 0.49].…”
Section: Resultsmentioning
confidence: 99%
“…27,51,52 Five studies examined the relationship of the 6MWT with QOL, 46,[54][55][56][57] with 3 studies showing some relationship with QOL pretransplant. 46,55,56 One study 26 examined and showed a relationship between the 6MWT and delisting of transplant candidates. More information about the direction of these relationships is presented in Table S1 (SDC, http://links.lww.…”
Section: Relationship With Clinical Outcomes In Lung Transplant Candi...mentioning
confidence: 99%